Laboring to communicate: Use of migrant languages in COVID-19 awareness campaign in Qatar - Rizwan Ahmad (14585211) (2023)
This study examines the communication strategies employed by Qatar’s government in dealing with the COVID-19 pandemic. The study contributes to a growing body of work on the sociolinguistics of crisis communication. We focus on the use of South and Southeast Asian languages, spoken largely by blue-collar migrant workers, which are often seen as peripheral even though they are spoken by a large segment of the population. The deployment of these languages during Qatar’s COVID-19 awareness campaign assumes further significance against the backdrop of a series of measures taken by the government in the last few years to strengthen the status and use of Arabic. We analyze multilingual printed pamphlets, multilingual audio-visual communication through radio and social media, as well as interviews conducted with key figures who were part of the awareness campaign. Our examination of the availability, accessibility, acceptability, and adaptability of the multilingual awareness materials reveals that while the different languages and modes of communication were important in spreading awareness, equally critical, if not more, was who carried the information and in what forms. We show the significant roles community and religious leaders and social media influencers played in disseminating the awareness information to the diverse migrant language communities.  Other information  Published in: Multilingua License: http://creativecommons.org/licenses/by/4.0 See chapter on publisher's website: http://dx.doi.org/10.1515/multi-2020-0119